(untitled) (Journal of Dhaka Medical College, 2010)
Myasthenia gravis (MG) is the most frequent neuromuscular transmission disorder with incidence of 2-20 patients per million1. Its pathophysiology is autoimmune, with acetylcholine receptors (AChR) autoantibodies damaging the post-synaptic fold at the muscle membrane. MG often presents with isolated ocular symptoms, including diplopia and ptosis, at least at the onset. It is often challenging to confirm the diagnosis of MG. The most traditional diagnostic test for myasthenia gravis is the edrophonium / prostigmin test. However, with this test, false-positive results have been reported in other neurologic disorders like amyotrophic lateral sclerosis, botulism and brain tumour. Furthermore, it also carries a risk of serious cardiac adverse reactions. The ice pack test is a very simple, safe and cheap procedure that can be performed by the physician at the bedside. Considering that the pure ocular form of MG is frequently not detected by the traditional tests available, the ice pack test is an attractive diagnostic method. We describe two cases where the ice pack test was done at the bedside for the diagnosis of MG and then performed prostigmin test and reviewed the literature about this test. In conclusion, the ice pack test is an easy, safe, cheap and reliable test to be used at bedside in the MG suspected patients with ptosis. It is safer and can replace the edrophonium/ prostigmin test in MG with ptosis, since the specificity and sensitivity is 100% when compared. Key words: Myasthenia Gravis (MG); prostigmin test; occular manifestation. DOI: 10.3329/jdmc.v18i2.6268 J Dhaka Med Coll. 2009; 18(2) : 112-114